Implementasi Metode Pembelajaran Jigsaw Dalam Meningkatkan Keaktifan Belajar Siswa Kelas IV SD - Riska Yulia Citra Amanda; Lilian Slow (STKIP Melawi, 2026)
Abstract: This study shows that the implementation of the Jigsaw learning model is effective in increasing the learning activity of fourth-grade students at SDN 01 Balaikarangan. This improvement is evident in several key indicators, namely attention to learning, the ability to express opinions, participation in discussions, cooperation between students, and responsibility in completing assignments. Each student has an important role in both expert groups and home groups, so they are encouraged to understand the material independently and convey it back to their group mates. Group-based learning through the Jigsaw model can create a more dynamic, communicative, and collaborative classroom atmosphere. The mechanism of teaching each other between students provides a more meaningful learning experience while helping develop students' social and academic skills. Thus, the Jigsaw model can be used as an alternative effective learning strategy to increase learning activity and support the achievement of learning objectives in elementary schools. Keywords: Implementation, Jigsaw And Activeness Abstrak: Penelitian ini menunjukkan bahwa penerapan model pembelajaran Jigsaw efektif dalam meningkatkan keaktifan belajar siswa kelas IV SDN 01 Balaikarangan. Peningkaan ini tampak pada beberapa indikator utama, yaitu perhatian terhadap pembelajaran, kemampuan mengemukakan pendapat, partisipasi dalam diskusi, kerja sama antarsiswa, serta tanggung jawab dalam menyelesaikan tugas. Setiap siswa memiliki peran penting dalam kelompok ahli maupun kelompok asal, sehingga mereka terdorong untuk memahami materi secara mandiri dan menyampaikannya kembali kepada teman kelompok. Pembelajaran berbasis kelompok melalui model Jigsaw mampu menciptakan suasana kelas yang lebih dinamis, komunikatif, dan kolaboratif. Mekanisme saling mengajar antarsiswa memberikan pengalaman belajar yang lebih bermakna sekaligus membantu mengembangkan keterampilan sosial dan akademik siswa. Dengan demikian, model Jigsaw dapat dijadikan alternatif strategi pembelajaran yang efektif untuk meningkatkan keaktifan belajar dan mendukung pencapaian tujuan pembelajaran di sekolah dasar. Kata Kunci: Implementasi, Jigsaw dan Keaktifan